Fatty acid transfer from Yarrowia lipolytica sterol carrier protein 2 to phospholipid membranes - Falomir Lockhart, Lisandro J. (2009)
Sterol carrier protein 2 (SCP2) is an intracellular protein domain found in all forms of life. It was originally identified as a sterol transfer protein, but was recently shown to also bind phospholipids, fatty acids, and fatty-acyl-CoA with high affinity. Based on studies carried out in higher eukaryotes, it is believed that SCP2 targets its ligands to compartmentalized intracellular pools and participates in lipid traffic, signaling, and metabolism. However, the biological functions of SCP2 are incompletely characterized and may be different in microorganisms. Herein, we demonstrate the preferential localization of SCP2 of Yarrowia lipolytica (YLSCP2) in peroxisome-enriched fractions and examine the rate and mechanism of transfer of anthroyloxy fatty acid from YLSCP2 to a variety of phospholipid membranes using a fluorescence resonance energy transfer assay. The results show that fatty acids are transferred by a collision-mediated mechanism, and that negative charges on the membrane surface are important for establishing a "collisional complex". Phospholipids, which are major constituents of peroxisome and mitochondria, induce special effects on the rates of transfer. In conclusion, YLSCP2 may function as a fatty acid transporter with some degree of specificity, and probably diverts fatty acids to the peroxisomal metabolism.